EFEKTIVITAS REGIONAL COOPERATION AGREEMENT ON COMBATING PIRACY AND ARMED ROBBERY (ReCAAP) DALAM PENANGANAN KASUS PEMBAJAKAN KAPAL DAN PERAMPOKAN BERSENJATA DI ASIA TENGGARA TAHUN 2012-2015 - Shela Aprilia; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effectiveness of ReCAAP in handling cases of piracy and armed robbery in Southeast Asia by 2012-2015. The author focuses on the condition of the problem and the level of collaboration in ReCAAP own.Sources of this study was obtained through journals, books, theses, reports, press releases and websites that explain ReCAAP and effectiveness associated with operations in Southeast Asia using the perspective of neorealism and Effectiveness Theory Regime.In this study, the authors found that ReCAAP operate effectively in Southeast Asia, it can be seen from the complexity of problems that are not being met, either in the capacity to solve problems and a high level of collaboration that led to changes in the behavior of members and optimal achievement of technicalKeywords: Regime Effectiveness Theory, Piracy, Armed Robbery, Regional Cooperation on Combating Piracy and Armed Robbery (ReCAAP)